Nekotorye protivorechiya v razvitii sovremennoi teorii sporta - Sutula, V. A.; Tszin-Tyan, Y. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The modern theory of sports as the scientific direction, within the framework of which the sports are studied as the complete phenomenon, should be based on three equal in rights "whales": the sports pedagogics, the biology of sports, the philosophy of sports. The connection between these basic components can be expressed by the following triad: the pedagogics should answer the question "how to build a training process?". The biology of sports - "why it is necessary to build the training process by that way?". The philosophy of sports - "for what it is necessary to build the training process by that way?".